Movie Still From The Pearl - RKO Radio Pictures:::Creator::::::::::::
The Pearl movie still of Kino (Pedro Armendariz) and Juana (Maria Elena Marques.) A Caption reads: THE PEARL Juana and Kino dress in their finest clothes to go and sell the pearl. This scene filmed in Acapulco de Juarez, Guerrero, Mexico, North America. RESTRICTED USE Original in safe